Study of the efficacy of electrocoagulation in the removal of polyethylene terephthalate (PET) microplastics in synthetic wastewater: An experimental approach - Romero Zanabria, Jose David (2025)
This article provides an in-depth analysis of the efficacy of electrocoagulation as a method for the treatment of polyethylene terephthalate (PET) microplastics in synthetic wastewater, in response to the growing environmental concern caused by the contamination of aquatic ecosystems with microplastics, resulting from discharges from wastewater treatment plants. The research focused on the study of the influence of two key variables on the efficiency of the process, the electrical potential and the application time, a batch reactor specifically designed for this experiment was used. The results showed that electrocoagulation, when implemented for 60 minutes with an electrical potential of 30V, conditions identified as optimal in this study, manages to reduce the concentration of PET Mps from an initial concentration (CI) 0.28 g / L to a final concentration (CF) 0.005 g / L, which corresponds to a removal efficiency of 98.21%. Likewise, the method proved to be highly adaptable to variations in operating conditions, maintaining a removal efficiency greater than 60% even when both the time and the electrical potential are reduced to 30 minutes and 15V, respectively. When evaluating the joint interaction of these variables, a direct influence on the efficiency in the removal of PET MPs was found. However, the electrical potential showed a slightly greater impact compared to the application time. These findings reinforce the viability of electrocoagulation as a flexible and promising strategy for the treatment of microplastics in wastewater.